Pedagogical Content Knowledge on a Language Class (2021)
This article analyzes and interprets the components of Pedagogical Content Knowledge [PCK], in the practice of a teacher in a first-grade language lesson. The methodology was qualitative and interpretive, using observation and content analysis as techniques to collect and detail information. As a result, it highlights the manifestation in the totality of the components of PCK studied, and a preponderance of three of them in the class stands out: knowledge of strategies and representations for teaching, teacher effectiveness, and understanding of the evaluation. In effect, the teacher develops the class taking into account the comprehension of the strategy by inquiry, effectiveness through motivation and security to participate, evaluation processes through investigation, and appropriation of the subject considering the context.